Enhancing construction efficiency: assessing the values and barriers of integrating e-procurement with BIM - Sarmad Masoom; Hamza Shahid; Muhammad Shahzaib; Sohaib Naseer; Muhammad Irfan; Muhammad Ali Musarat; Abdulaziz Alotaibi (Journal of Asian Architecture and Building Engineering, 2025)
This study aims to analyze the influence of integrating e-procurement and Building Information Modeling (BIM) on the construction industry, focusing on its potential to enhance efficiency, collaboration, and project delivery while addressing key challenges. A quantitative approach was adopted, using a structured questionnaire survey to collect data from respondents affiliated with client, contractor, and consultant organizations. The analysis employed advanced techniques such as Interaction Coefficient (IC), Synergistic Contribution (SC), Dynamic Influence and Dependency analysis, Forecast Impact and Resilience analysis, System Dynamics Simulations and Scenario Analysis. The findings highlight key benefits, including enhanced quality, cost control, and increased efficiency, which streamline project execution and optimize resource management. However, barriers such as lack of interoperability, incomplete standards, and organizational resistance hinder widespread adoption. Technological, managerial, and regulatory factors drive these challenges. The study suggests that addressing these barriers through interoperability frameworks, standardized protocols, and stakeholder engagement can unlock BIM’s full potential. The results offer valuable insights for policymakers and industry stakeholders, emphasizing the importance of overcoming these challenges to realize the full benefits of BIM-integrated e-procurement. When combined with short-term improvements and long-term innovations, BIM-integrated e-procurement can be a transformative tool in the construction industry.